Effect of DASH Diet Versus Healthy Dietary Advice on the Estimated Atherosclerotic Cardiovascular Disease Risk - Marwa S. Said; Inas T. El Sayed; Eman E. Ibrahim; Ghada M. Khafagy (SAGE Publishing, 2021)
Introduction: Cardiovascular disease (CVD) is the most leading cause of mortality worldwide. Changes in diet can reduce subclinical cardiac injury and inflammation in parallel with reductions of other CVD risk factors. Aim: The study aimed to evaluate the beneficial effect of the DASH diet versus usual healthy dietary advice (HDA) on the estimated risk of atherosclerotic cardiovascular disease (ASCVD). Methods: It was a prospective interventional nonrandomized controlled study, conducted on 92 participants attending Family Medicine Outpatient Clinics, Cairo University. The participants were assigned to 2 dietary groups, the DASH and HDA groups, for 12 weeks. All subjects were subjected to anthropometric measurement, assessment of lipid profile, and the estimated cardiovascular risk pre-and post-intervention. Results: The estimated cardiovascular risk was reduced significantly in both the DASH and HDA groups, with no statistically significant difference between the 2 groups regarding the risk reduction. By comparing the percent change between pre and post-intervention in both DASH and HDA groups, the following are the results: BMI dropped by 6.5% versus 2.5%, systolic blood pressure decreased by 6.9% and 4.1%, fasting blood sugar dropped by 5.5% and 3.1%, total cholesterol dropped by 5.2% and 3.1%, LDL dropped by 8.2%, and 3.1%, and HDL increased by 8.2% and 2.4%, in DASH and HDA groups, respectively. Conclusion: Both the DASH diet and HDA are associated with improvement in CVD risk factors. Although better risk factors decline with the DASH diet, there was no statistically significant difference between the 2 groups.